Implementation of Lora and CoAP Protocol in Hydroponic Plant Water Pump Control - Nurwarsito, Heru; Pradana, Kevin Dion Andre (Journal of Information Technology and Computer Science, 2023)
Hydroponics is the cultivation of plants without using soil media, but using water media that contains nutrients and minerals. To observe the growth parameters of hydroponic plants, it is still necessary to come directly to the hydroponic site and provide the nutrients needed manually. In time efficiency, the use of Internet of Things (IoT) is needed so that there is no need to come directly to the hydroponic site. LoRa is a Low Power Wide Area Network (LPWAN) communication system. This research uses sensor nodes, middleware, and client nodes as well as the Constrained Application Protocol (CoAP) protocol for clients to access the value of sensors to control automatic pumps so that nutrients for plants can be given directly without the need to come to the hydroponic site. The result of the implementation is that the water pump control can run properly until the plants can be harvested. The performance testing is done so that LoRa can transmit data at a distance of 1 km with an RSSI value of -114 dBm.